Bronchopulmonary malinosculation: a case report - Kumar, Meera J.; Balakrishnan, Jayaprakash; Nair, Reshmi S. (International Journal of Research in Medical Sciences, 2021)
Pulmonary malinosculation, which include a broad spectrum of disorders that involve abnormalities in one or more of the three main components of the lung, namely, the airways and lung parenchyma, arteries and veins. A case of bronchopulmonary malinosculation was presented due to its rarity.